معاني كلمات الأضداد في سورة النّساء (دراسة وصفية تحليليّة لغوية): The Meanings Of Opposites Words In Surat Al-Nisa (A Descriptive Analytical Linguistic Study) - Nur Ila Ifawati; Danial Hilmi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Contemporarily, the study of al-Qur'an has a divine‘s value of presenting the work of literature. One of the studies that manifests in a variety of meanings is the existence of al-Adldaad which induces to multiple interpretations. Al-Adldaad's position occupies various conditions where linguistic studies need to explore this existence. This discussion is important, so that someone can understand the meaning of a word or expression correctly by paying attention to the sentence context. Based on this, the purposes of this article are to identify the al-Adldaad words in surah al-Nisa' and explain the meaning of the al-Adldaad words in a linguistic context. Researchers used qualitative method and descriptive approache. Data analysis technique using content analysis. The results of the study show that the words al-Adldaad in surah al-Nisa' theorically and practically (use) and their meaning are dominated by the words “baina/bainahuma” which mean “al-Wishool” and “al-Firooq”, the words